Risk of Malposition in a 56-Year-Old Female Lippes Loop IUD User: A Case Report - Sepriano, Muhammad Ardi Levrian; Susilo, Artha Falentin Putri; Sasotya, Raden Mas Sonny (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: The intrauterine device (IUD) stands as a widely utilized contraceptive modality globally, renowned for its effectiveness and long-term reliability. However, within the spectrum of potential complications, the occurrence of perforation, though rare, represents a significant concern due to its potential for serious sequelae. Perforation entails the unintended penetration of the uterine wall by the IUD, leading to its migration beyond the uterine cavity. Despite its gravity, perforation often presents as an asymptomatic phenomenon, with some cases remaining undetected for extended durations following insertion. Lippes loop IUD complications are relatively low risk like malposition, embedded, or perforation.Case Report: This study documents a notable case involving a 56-year-old, P1A0, who had been utilizing an intrauterine device for a remarkable 31-year period. Referred from Hermina Arcamanik Hospital, the patient sought intervention for IUD removal, notwithstanding the absence of associated symptoms. Notably, physical examination and laboratory analyses yielded unremarkable findings, highlighting the latent nature of this complication. Further diagnostic elucidation through ultrasound examination confirmed the presence of a Lippes Loop (LL) IUD embedded within the uterine cavity. The intrauterine device (IUD) became embedded, rendering it impossible to remove. The IUD extraction is performed using hysteroscopy. Subsequent peri hysteroscopic extraction of the IUD unveiled partial embedding within the posterior uterine cavity, necessitating precise intervention to mitigate potential complications. Fortunately, postoperative surveillance revealed an absence of pain or hemorrhagic complications, culminating in the patient’s discharge on the first postoperative day. Conclusion: Constituted primarily of plastic material, LL IUDs offer prolonged utility devoid of significant adverse sequelae, underscoring their role as a viable contraceptive option with a slight risk of embedded for women seeking enduring contraception.Risiko Malposisi pada Akseptor Lippes Loop IUD pada Wanita Usia 56 Tahun: Sebuah Laporan KasusAbstrakPendahuluan: Alat Kontrasepsi Dalam Rahim (AKDR) merupakan metode kontrasepsi yang banyak digunakan di seluruh dunia karena efektivitas dan keandalannya dalam jangka panjang. Namun, di antara berbagai potensi komplikasi, perforasi menjadi salah satu kekhawatiran utama meskipun jarang terjadi, mengingat potensi dampak serius yang dapat ditimbulkannya. Perforasi terjadi ketika IUD secara tidak sengaja menembus dinding rahim, menyebabkan migrasi IUD keluar dari kavitas uterus. Meskipun serius, komplikasi ini sering ersifat asimtomatik dan tidak terdeteksi dalam jangka waktu lama setelah pemasangan. Komplikasi IUD tipe lippes loop dapat terjadi seperti malposisi, embedded atau perforasi, tetapi pada kasus yang jarang. Presentasi Kasus: Studi ini melaporkan kasus menarik pada seorang wanita berusia 56 tahun, P1A0, yang telah menggunakan IUD selama 31 tahun. Pasien dirujuk dari RS Hermina Arcamanik untuk menjalani prosedur pengangkatan IUD, meskipun tidak mengalami gejala terkait. Pemeriksaan fisik dan analisis laboratorium tidak menunjukkan kelainan, menekankan sifat laten komplikasi ini. Pemeriksaan ultrasonografi lebih lanjut mengonfirmasi keberadaan IUD jenis Lippes Loop (LL) yang tertanam di dalam kavitas rahim. Prosedur histeroskopi dilakukan karena IUD tertanam di dalam kavitas rahim sehingga membuat IUD sulit untuk diekstraksi secara normal. Saat prosedur histeroskopi, ditemukan bahwa sebagian IUD tertanam di dinding posterior rahim, memerlukan intervensi presisi guna mencegah komplikasi lebih lanjut. Pemantauan pascaoperasi tidak menunjukkan adanya nyeri atau komplikasi perdarahan, dan pasien dipulangkan pada hari pertama setelah operasi.Kesimpulan: Karena terbuat dari bahan dasar plastik, IUD LL menawarkan masa pemakaian yang lama tanpa menimbulkan efek samping yang signifikan, menjadikannya pilihan kontrasepsi yang andal, namun dengan risiko kecil terjadi embedded bagi wanita yang mencari solusi kontrasepsi jangka panjang.Kata kunci: Alat kontrasepsi dalam rahim, embedded, lippes loop, risiko